Pelagic amphipods (Amphilochidea, Hyperiidea and Senticaudata) from the Pacific of Costa Rica: new records and an updated list of species - Violante-Huerta, Marco (2021)
Few studies of zooplankton have been carried out in Costa Rica that address pelagic amphipods; the species list prior to this work includes only 41 species from the suborder Hyperiidea. The aim of this paper was to update the species list of pelagic amphipods from the Pacific of Costa Rica, and record previously unknown species from the country. In July 2012, zooplankton sampling was carried out in the waters near Cocos Island, Costa Rica, at 26 oceanographic stations. A total of 13 pelagic amphipod species from the suborders Amphilochidea (1), Hyperiidea (11) and Senticaudata (1) were identified in the Pacific waters of Costa Rica. These new records increase the known total of pelagic amphipod species from the Pacific of Costa Rica to 54 species, which suggests a need to further explore the diversity of these organisms in the region.